The Karl Muck scandal : classical music and xenophobia in World War I America - Burrage, Melissa D., 1962- (Eastman studies in music., 2019)
The demonization, internment, and deportation of celebrated Boston Symphony Orchestra conductor Dr. Karl Muck, finally told, and placed in the context of World War I anti-German sentiment in the United States.